Application of Indocyanine Green Angiography in Bilateral Axillo-Breast Approach Robotic Thyroidectomy for Papillary Thyroid Cancer - Ouyang, Hui; Wang, Baojia; Sun, Botao; Cong, Rong; Xia, Fada; Li, Xinying (Frontiers in Endocrinology, 2022)
Background: Indocyanine green angiography (ICGA) has been used to identify and preserve the parathyroid glands (PGs), and to evaluate PGs viability and function during thyroid surgery. However, evidence on the utilization of IGCA in thyroid cancer and robotic surgery is lacking. The efficacy of IGCA remains to be evaluated in PTC patients undergoing bilateral axillo-breast approach robotic thyroidectomy (BABA RT) and central neck dissection (CND). Methods: From March 2020 to August 2021, 81 papillary thyroid cancer (PTC) patients receiving total thyroidectomy and CND were enrolled in this retrospective analysis. An intravenous bolus of 7.5 mg ICG was administrated three times in the ICGA group (n=34). Medical records were reviewed and analyzed, including the baseline characteristics, surgical parameters, PGs-related parameters, and perioperative PTH and calcium levels. Results: The mean number of total identified PGs and preserved PGs were significantly more in the ICG group than in the control group (3.74±0.45 vs. 3.15±0.55, P<0.001; 3.12±0.64 vs. 2.74±0.57, P=0.007, respectively), as were PTH and calcium levels on POD 1 (23.16±18.32 vs. 6.06±7.74, P=0.039; 2.13±0.11 vs. 2.08±0.08, P=0.024, respectively). While there were no differences in PTH levels on POD 30. Additionally, patients with at least one well vascularized PG had higher ioPTH 3 and PTH on POD 1, which significantly suggested the absence of postoperative hypocalcemia. Although not statistically significant, ICGA seemed superior to relative ioPTH decline and ioPTH 3 in predicting postoperative hypocalcemia. Conclusion: In PTC patients undergoing BABA RT and CND, ICGA is a simple, safe, effective, and cost-effective tool in better identification and preservation of PGs as well as evaluation of PGs viability and function, with the potential to preserve more PGs, guide more appropriate autotransplantation, and accurately predict postoperative hypocalcemia.